2017
DOI: 10.3357/amhp.4768.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological Evaluation of Integrated Resistance and Aerobic Training During 70-Day Bed Rest

Abstract: INTRODUCTION We evaluated ophthalmic changes in healthy individuals who underwent integrated resistance and aerobic training (iRAT) during 70-day 6° head-down-tilt (HDT) bed rest (BR). METHODS Participants were selected using NASA standard screening procedures. Standardized NASA BR conditions were implemented. Subjects were randomly assigned to the iRAT protocol or no exercise during HDTBR. Weekly ophthalmic examinations were performed in the sitting (pre/post-BR only) and HDT (BR only) positions. Mixed-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Although we and others have reported data from this (19) and similar (21,22) bed rest studies, to our knowledge, none of the data reported here have been published previously (and certainly no data pertaining to dietary APro:K effects on bone).…”
Section: Bed Restmentioning
confidence: 48%
See 1 more Smart Citation
“…Although we and others have reported data from this (19) and similar (21,22) bed rest studies, to our knowledge, none of the data reported here have been published previously (and certainly no data pertaining to dietary APro:K effects on bone).…”
Section: Bed Restmentioning
confidence: 48%
“…Comparison data are reported here from a 70-d bed rest study evaluating exercise as a countermeasure to physiologic effects of simulated microgravity (19). These data are from one of a series of bed rest studies conducted at the University of Texas Medical Branch (UTMB) in Galveston, TX (20).…”
Section: Bed Restmentioning
confidence: 99%
“…One study demonstrated a small decrease in IOP (−1.61 mmHg) after a short session of weightlifting in 25 healthy volunteers in supine position with 85% top load for 8 repetitions [ 31 ]. Taibbi et al [ 32 ] studied the effects of a 70-day HDBR on ophthalmic changes with some specific countermeasures such as integrated resistance and aerobic training in 6 controls and 9 exercisers. The authors declared that both controls and exercisers exhibited a rise in IOP during HDBR (respectively, +1.38 mmHg and +1.63 mmHg), measured with iCare IOP.…”
Section: Discussionmentioning
confidence: 99%
“…The authors described a preserved retinal thickness, ganglion cell layer and choroidal thickness after weightlifting. However, Taibbi et al [ 32 ] also studied the effects of integrated resistance and aerobic training on circumpapillary RNFL and peripapillary retinal thicknesses after 70 days of HDBR. In this study, spectralis OCT revealed an increase in circumpapillary RNFLT (+1.33 µm) in 15 subjects (6 controls and 9 exercisers) after HDBR.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the atrophying effect of microgravity on skeletal muscle, astronauts undergo 2.5 h of intensive resistance and aerobic exercise nearly every day onboard the ISS (67). However, implementation of NASA's integrated resistance and aerobic training (iRAT) protocol during 70-day non-hypercarbic strict 6 • HDTBR was not associated with a significant difference in retinal thickening or signs of optic disc edema compared to a control HDTBR group who did not exercise, though IOP was slightly higher (<1 mm Hg) in the exercise group (68). Interestingly, 15 • head down tilt for less than an hour was associated with a decrease in IOP in subjects undergoing either moderate-intensity aerobic, resistance, or high-intensity interval aerobic exercise (69).…”
Section: Countermeasure Testing and Monitoring Development In Head-domentioning
confidence: 98%